Daniel and the Diadochi - Gallagher, Edmon L. (Journal of Biblical literature, 2022)
Three verses in the book of Daniel describe the Hellenistic world as divided into four segments (Dan 8:8, 22; 11:4). The history of interpretation of the book of Daniel displays a remarkable readiness, even among critical scholars, to take this scheme literally and to press Hellenistic history into the mold supplied by Daniel's apocalyptic visions. Daniel commentators agree, for instance, in understanding the four new horns of the goat in Dan 8 as representative of the Diadochi, the successors of Alexander the Great in the late fourth century BCE, but they disagree on precisely which Diadochi the apocalyptic seer had in mind. An examination of our classical sources for early Hellenistic history, particularly the most detailed source, Diodorus Siculus, demonstrates the near futility of trying to identify precisely four parts of the post-Alexander Macedonian Empire. In the present article, I find a symbolic interpretation of the number four to be the most satisfying, but I also make some suggestions for how to understand the number literally as a representation of the Hellenistic world. Nevertheless, commentators taking the number "four" in Dan 8:8, 22; 11:4 as a straightforward and simple reference to a historical reality have underestimated the chaos of the decades following Alexander's death.